Instant electrode fabrication on carbon-fiber-reinforced plastic structures using metal nano-ink via flash light sintering for smart sensing. (July 2015) - Takahashi, Kosuke; Namiki, Kensuke; Fujimura, Takahiro; Jeon, Eun-Beom; Kim, Hak-Sung
Abstract: The electrical-resistance-change method (ERCM) is a potential smart-sensing technique for carbon-fiber-reinforced plastic (CFRP) structures. However, a practical way to fabricate electrodes on CFRP structures, such as ink-jet printing with metal nano-inks, is necessary to reduce the time required for the process. As metal nano-inks can be sintered in a few milliseconds under ambient conditions using white-flash-light irradiation from a xenon lamp, the parameters of flash-light sintering such as light energy, duration, and number of pulses were investigated. The light intensity, which is the light energy divided by duration, was found to be an indicator of whether low electrical resistance was attained along with strong adhesion to the CFRP plate. The contact resistance between the electrode and CFRP plate was also examined in a tensile test to confirm the durability. The electrode sintered by flash light with the properly selected parameters exhibited high quality and strain monitoring capability.